The influence of medical and social risk factors on the development of hypertension in the adult population at the regional level - Z. V. Lashkul; D. A. Lashkul (Zaporožskij Medicinskij Žurnal)
The aim of the study was to investigate the impact of medical and social risk factors (RF) on the development of arterial hypertension (AH) in the adult population at the regional level (Zaporizhzhia, Ukraine).